Comparative study of maternal and perinatal outcome in pregnancies with and without umbilical cord around foetal neck - Sonawane, Pundalik K.; Bhadra, Deep M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Umbilical cord around neck of the foetus is called the nuchal cord. The aims and objectives are to find out the incidence of nuchal cord around foetal neck at delivery, and to compare and evaluate intrapartum and postpartum maternal and foetal outcome in those with or without nuchal cord at delivery. Methods: It is a prospective cross-sectional study conducted at tertiary care hospital for period of 12 months. Of 1380 patients, 934 patients were enrolled in present study after meeting the inclusion and exclusion criteria of which 150 patients were included in study group who delivered with nuchal cord and 784 patients in control group who delivered without nuchal cord. Results: Present study showed 18.84% incidence of nuchal cord at delivery. Duration of labour was 6.51hrs in study group and 6.15hrs in control group and the difference was statistically significant. Rest of the intrapartum and postpartum events were statistically not significant. Mean length of cord was more in patients delivered with loop of cord around foetal neck as compared to another group and it is statistically significant. Conclusions: Nuchal cord is a common finding at the time of delivery. However, it is per-se not an indication of LSCS and it only increases the operative morbidity.